A Textbook of fluid mechanics and hydraulic machines - Bansal, R.K (A. Saurabh and Co, 1985)
A Textbook of fluid mechanics and hydraulic machines / Bansal, R.K.. -- Delhi: A. Saurabh and Co., 1985 532 B212e2 2nd ed.